Quality higher education drives employability in the Middle East - Nauffal, Diane (2018)
Purpose The purpose of this paper is to analyse and explain the high rates of employability of one group of Middle East youth by focussing on liberal arts and soft skills education as an integral part of quality higher education. Design/methodology/approach This paper employs the survey research method using questionnaires, focus groups and interviews to understand the labour market dynamics in Lebanon and explore factors that correlate positively with gainful employment with a special focus on the graduates of an institution that emphasises the liberal arts and soft skills training. Findings The paper finds that quality higher education – particularly with a focus on soft skills and internships – boosts the potential of graduates to secure their first jobs after graduation. Research limitations/implications Reliable data on higher education, employability and youth are scarce in Lebanon and the region. The paper is based on one labour market study in Lebanon while seeking to extrapolate to Lebanese youth as a whole as well as reflect on employability and youth in the Middle East region. Practical implications The paper demonstrates support for improving quality in higher education as well as making soft skills training and the liberal arts critical components for increased employability of youth in Lebanon and the Middle East. Originality/value The paper is innovative in its reliance on primary data from a labour market survey as such data are scarce in Lebanon. In addition, advocacy for soft skills training and the liberal arts in the midst of focus on science, technology, engineering and mathematics and other professional education at the university level is rare in the Middle East.